2018
DOI: 10.1021/acs.analchem.8b02098
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Droplet Extraction and Pico-ESI-MS Allows the Identification of Metabolites from Single Cancer Cells

Abstract: We have combined droplet extraction and a pulsed direct current electrospray ionization mass spectrometry method (Pico-ESI-MS) to obtain information-rich metabolite profiling from single cells. We studied normal human astrocyte cells and glioblastoma cancer cells. Over 600 tandem mass spectra (MS) of metabolites from a single cell were recorded, allowing the successful identification of more than 300 phospholipids. We found the ratios of unsaturated phosphatidylcholines (PCs) to saturated PCs were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 50 publications
0
57
0
Order By: Relevance
“…Among those omics, the proteome and metabolome respond to external stimuli more rapidly and usually are harder to be detected or identified due to their complex structures and low biomarker abundances in a single cell 11 . Mass spectrometry (MS) has become a method of choice for single-cell metabolome analysis in consideration of its high sensitivity and high structural identification capabilities [12][13][14][15][16][17][18][19][20] .…”
mentioning
confidence: 99%
“…Among those omics, the proteome and metabolome respond to external stimuli more rapidly and usually are harder to be detected or identified due to their complex structures and low biomarker abundances in a single cell 11 . Mass spectrometry (MS) has become a method of choice for single-cell metabolome analysis in consideration of its high sensitivity and high structural identification capabilities [12][13][14][15][16][17][18][19][20] .…”
mentioning
confidence: 99%
“…A subsequent study employed pulsed direct current ESI-MS liquid microextraction to allow more spectra to be recorded from each cell. 21 Using this approach, the authors were able to acquire over 600 MS/ MS spectra from a single cell. It was found that the number of unsaturated phospholipids increased in glioblastoma cells compared to normal astrocyte cells.…”
Section: Ambient Ionization Of Single Cellsmentioning
confidence: 99%
“…It was found that the number of unsaturated phospholipids increased in glioblastoma cells compared to normal astrocyte cells. 22 A different route for desorbing material from single cells on a surface is to use laser desorption. In laser desorption/ionization droplet delivery (LDIDD) MS a focused UV laser is directed towards the cell surface to desorb/ionize the cell components.…”
Section: Ambient Ionization Of Single Cellsmentioning
confidence: 99%
“…Zhang and coworkers recently described a combined droplet extraction and a pulsed direct current ESI-MS method to record over 600 tandem mass spectra from a single human astrocyte cell and identified over 300 phospholipids. 143 Yin et al extracted picoliter volumes of material from live Allium cepa cells using electroosmotic extraction and a hydrophobic MS compatible electrolyte followed by nano-ESI analysis to identify more than 50 metabolites. 144 Efficient partitioning of hydrophilic and hydrophobic analytes was observed into the aqueous and hydrophobic electrolyte phase respectively providing additional insight on the molecular properties.…”
Section: Metabolomics and Lipidomicsmentioning
confidence: 99%